2005
DOI: 10.1021/jp054248s
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Vibrational and Optical Spectra of Methylene-Bridged Oligofluorenes

Abstract: We report a systematic characterization of methylene-bridged fluorene oligomers constructed of two, four, six, and eight aromatic rings using time-dependent density functional theory (TDDFT), the ab initio approximate coupled-cluster singles and doubles (CC2) method, and semiempirical spectroscopic Zerner's intermediate neglect of differential overlap method (ZINDO/S). Geometry optimizations have been performed for the ground state and for the first electronically excited state. Vertical excitations and the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 39 publications
(66 reference statements)
2
90
0
1
Order By: Relevance
“…The extrapolated vertical excitation energy is somewhat lower than the experimental values 18 (3.20 eV in film and 3.26 eV in THF solution). Previous experience with TD-DFT/B3LYP calculations on methylenebridged oligofluorenes 47 showed that this approach underestimated the extrapolated excitation energies. Another reason might be that the effective conjugation length is smaller because of defects in the polymer chains.…”
Section: Vertical Excitation Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extrapolated vertical excitation energy is somewhat lower than the experimental values 18 (3.20 eV in film and 3.26 eV in THF solution). Previous experience with TD-DFT/B3LYP calculations on methylenebridged oligofluorenes 47 showed that this approach underestimated the extrapolated excitation energies. Another reason might be that the effective conjugation length is smaller because of defects in the polymer chains.…”
Section: Vertical Excitation Energiesmentioning
confidence: 99%
“…Thus, major progress in the accuracy of the structural description of excited states is expected beyond the CIS approach, which had to be used for that purpose so far. This work also relies on experience with previous investigations comparing TD-DFT with the approximate coupled cluster singles and doubles method (CC2) 44 in combination with the resolution of the identity (RI) method 45,46 for oligo-fluorenes, 47 oligo-paraphenylenes (Lukeš, V.; Aquino, A.; Kauffmann, H. F.; Lischka, H. J Chem Phys, to be submitted) and on excited-state proton transfer systems. 48 In our approach the properties (UV, fluorescence spectra, and radiative lifetime) of a series of oligomers with increasing chain length is computed following by extrapolation to infinite chain length.…”
Section: Introductionmentioning
confidence: 99%
“…The average lifetime (t) of OMDPP solution in THF was calculated to be 5.567 ns, which was higher than that of PMDPP (3.543 ns) and lower than that of the monomer MDPP (6.006 ns). It indicates that the longer chain length tended to decrease the average lifetime, which was probably caused by a rapid increase in nonradiative decay as the conjugation length increased [43,44]. Additionally, the comparison of the average fluorescence lifetimes in different solvents showed that the fluorescence lifetime of OMDPP was not significantly dependent on the solvent polarity.…”
Section: Properties Of Omdppmentioning
confidence: 95%
“…The emission transitions of all the studied product compounds are assigned to S 1 / S 0 , composed of L / H. During the chemical modications based on the coumarin core in this work, the changing trends of the emission spectra are in accordance with the results of the OPA spectra. The uorescence lifetime (s) and uorescence radiation rate (K r ) for spontaneous emission are calculated by employing the Einstein transition probabilities according to the formulae in (4) and (5), 55,56 and are also shown in Table 3:…”
Section: Fluorescence Propertiesmentioning
confidence: 99%